Penggunaan Rumput Laut (Gracilaria verrucosa) sebagai Agen Biokontrol pada Polikultur Udang Vaname (Litopenaeus vannamei) untuk Mencegah Infeksi Vibrio harveyi - Ardana Kurniaji; Anton Anton; Yunarty Yunarty (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
This study aimed to examine polyculture of seaweed and vaname shrimp in laboratory scale to prevent V. harveyi infection. Study was conducted with a completely randomized design by 3 treatments and 3 repetations. Application of seaweed were 800 grams (P8), 400 grams (P4) and without seaweed (control). Challenge test was carried out for 10 days with bacteria concentration of 106 cfu/ml/ind in 10 shrimp using aquarium containing 100 liters of sea water. The result showed that polyculture of seaweed and shrimp could not maintain the survival rate of shrimp significantly but could suppress the population of V. harveyi in waters. Survival rate respectively from control, P4 and P8 were 60.0%, 73.3%, 76.7%. Population of bacteria in treatment was lower than control on 10th days after seaweed stocking until challenge test. Aplication of seaweed could also accelerate shrimp recovery time from bacterial infections observed in clinical symptoms that return to normal on 9th days after challenge test. Total hemocyte count (THC) were better observed in shrimp cultured seaweed on 10th days after challenge test, and differential hemocytes count (DHC) were better on 5th days after challenge test. Polyculture of seaweed and shrimp has potential to improve shrimp health status.